2005
DOI: 10.1007/s10529-005-1775-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural network designs for poly- ?-hydroxybutyrate production optimization under simulated industrial conditions

Abstract: Improvement of the fermentation efficiency of poly-beta-hydroxybutyrate (PHB) may make it competitive with chemically synthesized petroleum-based polymers. One step toward this is optimization of fluid dispersion and the feed rates to a fed-batch bioreactor. In a recent study using a fermentation model, dispersion corresponding to a Peclet number of approximately 20 was shown to maximize the productivity of PHB. Here further improvement has been investigated using neural optimization. A comparison of seven neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…While the recurrent neurons and information recycle improve the accuracy of an Elman network, they reduce its speeds of convergence during training and responses to unseen situations. Nevertheless, the Elman network is the best choice, as previous results [8,34,39,40] and the present investigation have shown.…”
Section: Kinetic Modelssupporting
confidence: 62%
See 2 more Smart Citations
“…While the recurrent neurons and information recycle improve the accuracy of an Elman network, they reduce its speeds of convergence during training and responses to unseen situations. Nevertheless, the Elman network is the best choice, as previous results [8,34,39,40] and the present investigation have shown.…”
Section: Kinetic Modelssupporting
confidence: 62%
“…Sometimes it is helpful to include some bias neurons in these layers so as help the network ride over local minima or shallow troughs in its quest for a global optimum. Obviously the neurons and the flow of signals between them may be arranged in different configurations, and previous studies [8,34,39,40] have demonstrated that an Elman neural network is the most suitable for a reactor with finite dispersion. Such a network has the architecture shown in Fig.…”
Section: Kinetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, increased complexity, linked to a lack of detailed knowledge of the metabolism, limit their applicability. This limitation can be overcome to some extent through the use of artificial neural networks, which have been applied to model a great number of systems, including PHB synthesis [31]. They do not require a rigorous mathematical description but rather rely on an exhaustive training methodology, with solutions coming from a heuristic search.…”
Section: Though Many Bacteria Have Been Isolated and Characterised Asmentioning
confidence: 99%
“…The method combines "first principles models" with modular artificial neural networks trained by the EM (Expectation-Maximization) algorithm (for details the reader should consult the works of Jordan and Jacobs 148 and Xu et a1. 149 ). The modular networks were used in order to treat the 'cells system' as a "highly complex network of metabolic reactions organized in modular pathways".…”
Section: Neural Network and Hybrid Models In Modelling Of Phas Biosymentioning
confidence: 99%